7 - ( 11 + x - 13 ) : 2 ??? 2/3 = 2
7 - ( 11 + x - 13 ) : 2 . 2/3 = 2
( 11 + x - 13 ) : 2 . 2/3 = 7 - 2
( 11 + x - 13 ) : 2 . 2/3 = 5
( 11 + x - 13 ) : 2 = 5 : 2/3
( 11 + x - 13 ) : 2 = 7,5
11 + x - 13 = 7,5 . 2
11 + x - 13 = 15
11 + x = 15 - 11
11 + x = 14
x = 14 - 11
x = 13
(11 - 13 +x ) : \(\frac{22}{3}\)=7- 2
(11 - 13 +x ) : \(\frac{22}{3}\)=5
(-2 + x ) :\(\frac{22}{3}\)=5
-2 + x = 5 x \(\frac{22}{3}\)
-2 + x = \(\frac{110}{3}\)
x=\(\frac{110}{3}\)- (-2 ) =\(\frac{116}{3}\)
(11+x-13) : \(\frac{22}{3}\)= 7-2
(11+x-13) : \(\frac{22}{3}\)= 5
(11+x-13)= 5 x \(\frac{22}{3}\)
(11+x-13)= \(\frac{110}{3}\)
x-13= \(\frac{110}{3}\)-11
x-13= \(\frac{77}{3}\)
x= \(\frac{77}{3}\)+13
x=\(\frac{116}{3}\)